2015
DOI: 10.1155/2015/298107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CAG Repeat Polymorphism on the Targets of Testosterone Action

Abstract: In the last decade, ample evidence has demonstrated the growing importance of androgen receptor (AR) CAG repeat polymorphism in andrology. This genetic parameter is able to condition the peripheral effects of testosterone and therefore to influence male sexual function and fertility, cardiovascular risk, body composition, bone metabolism, the risk of prostate and testicular cancer, the psychiatric status, and the onset of neurodegenerative disorders. In this review, we extensively discuss the literature data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 106 publications
4
51
0
3
Order By: Relevance
“…Так, исследования последних лет показали важную роль андрогенного дефицита у мужчин в развитии сердечно-сосудистых заболеваний и ЭД [15,16]. Установлено, что геномные эффекты тестостерона обусловлены по-лиморфизмом гена рецептора андрогенов [17]. Учитывая взаимосвязь полиморфизма гена рецептора андрогенов и ЭД [18], вызывает интерес определение его влияния на время наступления максимальной вазодилятации, что дает предпосылки для проведения новых исследо-ваний.…”
Section: результаты и обсуждениеunclassified
“…Так, исследования последних лет показали важную роль андрогенного дефицита у мужчин в развитии сердечно-сосудистых заболеваний и ЭД [15,16]. Установлено, что геномные эффекты тестостерона обусловлены по-лиморфизмом гена рецептора андрогенов [17]. Учитывая взаимосвязь полиморфизма гена рецептора андрогенов и ЭД [18], вызывает интерес определение его влияния на время наступления максимальной вазодилятации, что дает предпосылки для проведения новых исследо-ваний.…”
Section: результаты и обсуждениеunclassified
“…17 Long (CAG) n repeats have been associated with decreased AR transactivation activity and weaker transcriptional potential than short repeats. 18 CAG expanded repeats of at least 40 have been found in Kennedy disease, a neurodegenerative syndrome also characterized by androgen insensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,21 In contrast, a meta-analysis suggested that a shorter (CAG)n repeat polymorphism in Caucasians and Asians might increase the risk of prostate cancer compared with the longer (CAG)n repeat.…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphic sequence of the CAG repeat usually varies in number from 10 to 35, and encodes polyglutamine stretches of AR transactivation domain [10,11]. The majority of the findings suggest that the CAG number is negatively correlated to the transcriptional activity of AR, and as a result, to the effects of testosterone [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the findings suggest that the CAG number is negatively correlated to the transcriptional activity of AR, and as a result, to the effects of testosterone [10,12,13]. This relationship has also been evaluated in regard to the metabolic effect.…”
Section: Introductionmentioning
confidence: 99%